Randomized controlled trials are needed to close the evidence gap in the prevention of preterm birth - Emma Kwegyir-Afful; Sharea Ijaz; Kimmo Räsänen; Jos Verbeek (Nordic Association of Occupational Safety and Health (NOROSH), 2014)
Prematurity (<37 weeks gestation) is among the major determinants of infant morbidity and mortality (1). Within developing countries, where the condition is of major public health importance, incidence is around 19% versus 5-7% in developed nations (2). The global estimation of preterm delivery in 2005 was 9.6% of all births, which is a total of 12.9 million, 11 million of which were from Africa and Asia. About 28% of infant deaths occurring within the first seven days of life are a result of prematurity (3). Apart from the negative health implications of prematurity, the monetary cost is very alarming, with America alone spending over $26.2 billion on medical and educational interventions in addition to the cost of productivity loss (3). Despite global and local achievements in the survival rate of premature infants, the rate of prematurity keeps rising (4). The role of women in society has changed dramatically as today´s woman has a higher chance of going to school and getting employed outside the home than her mother (5). There is plausibility of heavy lifting (>5 days per week) in the causal pathway of premature delivery (6). Long working hours and heavy lifting are alleged to be associated with preterm delivery (7). Whilst some studies conclude there is a causal link between heavy lifting and preterm birth, another study concluded that, regardless of the exposure periods and the frequency of lifting, there is no significant association between heavy lifting and preterm birth (8). In a recent National Birth Cohort in Denmark, researchers published in the Scandinavian Journal of Work, Environment and Health concluded that occupational lifting of medium-to-heavy loads can lead to pelvic pain during pregnancy (9) whilst pelvic pain is a common signal of labor initiation. Interventions, such as health education, maternity leave, or reassignment to a less-physical task, are already in place in most Western countries to prevent exposure to heavy lifting at work among pregnant women. However, it is unclear which intervention produces better pregnancy outcomes. A systematic review (10) on the effects of bed rest as a preventive measure of preterm birth compared to no intervention among high-risk singleton pregnant women found no evidence to support this preventive measure. No other reviews on the comparative effectiveness of preventive measures for heavy lifting in preventing preterm birth were found. We therefore performed a systematic review of the published literature to locate evaluation studies of interventions to prevent heavy lifting during pregnancy. We searched for randomized or quasi-randomized controlled trials (RCT/quasi RCT) comprising pregnant employees exposed to lifting tasks, which evaluated an intervention aimed at decreasing lifting exposure and the effects on the incidence of prematurity. Based on these inclusion criteria we developed a search strategy and searched the databases Medline (via PubMed), Scopus, and CINAHL up to 28 June 2012 (see appendix for full search strategy). Two authors independently scrutinized the references for eligible trials but none fulfilled our inclusion criteria. A further search of reference lists of potentially relevant studies also failed to identify any RCT. Thus, the hypothesis that an intervention that decreases heavy lifting exposure among pregnant woman may have a positive impact on pregnancy outcomes could be not proven either right or wrong. We went strictly for RCT because of the quality in terms of study design (11) as rigorous procedures are carried out to establish the cause and effect relationship between an outcome and intervention (12). Nevertheless, our search did yield five observational studies that did not fit the inclusion criteria (RCT, pregnant employees as subjects, exposure to heavy-lifting tasks, and an intervention aiming at decreasing lifting exposure). Three of the studies investigated a causal association between preterm birth and heavy lifting whilst two were intervention studies. The three exposure studies (6, 13, 14) indicated a negative impact of occupational exposure to strenuous physical activities on gestational age. One literature review suggested that exercise could be beneficial and an observational evaluation study concluded that current legislation in Germany sufficiently protects pregnant women against preterm birth (15, 16). However, their lack of validity and greater margins of errors associated with the studies' designs make it difficult to rely on these observational studies. Existing systematic reviews of exposure are inconclusive on the subject matter. A meta-analysis indicated a statistically significant association between preterm birth and physically demanding work (5). Similarly, a systematic review (17) suggested a possible association between lifting and prematurity. In contradiction to these results, a third systematic review (18) refuted an association between lifting, especially during the first trimester, and premature delivery. This review was recently updated and came to similar conclusions (19). In spite of this, another Scand J Work Environ Health systematic review of the risk of miscarriage due to exposure to lifting during pregnancy cautions against lifting high loads during pregnancy (20). A phenomenon that characterized the identified primary studies was misclassification of exposure. The flaws in the estimation of especially the exposure severely hamper the drawing of strong conclusions in these studies and reviews. In almost all the studies, women self-reported their lifting exposure retrospectively or prospectively. It is unsure if the subjective measurement of exposure leads to non-differential misclassification. It has been argued that differential misclassification usually leads to an underestimation of the relation between exposure and outcome if there is any, but this is surrounded by uncertainty especially when exposure is on a continuous scale (21). It could be that misclassification is differential in case-control studies. Among cases, lifting exposure could be better remembered and reported as a result of recall bias. Therefore, there is a need for a high quality evaluation study in which a group of pregnant women with heavy lifting exposure are subjected to an intervention that decreases the exposure while a second group of unexposed women serves as a control. Such a study would provide reliable evidence for both an effect of the intervention and a causal relation (22). There are several possible explanations for the absence of high quality studies to support practice. To start, financial support is a major factor in every research. A substantial amount of money is required to conduct a high quality study. In low- and middle-income countries, where strenuous physical activity and premature birth are common occurrences (3, 6), access to finance to conduct research is always a challenge as evidenced by the "10/90 gap", which indicates only 10% of global resources are earmarked for health research addressing 90% of global disease burden (23). Secondly, ethical considerations can also be a limiting factor. Human lives are involved and there may be ethical issues as to who should and should not be advised to avoid heavy lifting given the current uncertainty about the evidence necessitating precautionary measures (5). Thirdly, an RCT requires recruitment of participants from the first trimester to determine the consequences of varied exposure to strenuous work during the three different trimesters, however, the chances of attrition can be high due to the length of the study. Finally, in high income countries where health research is more common, there already exists legislation on maternity leave that protects pregnant women and therefore researchers may not have enough motivation to carry out such studies. Education to decrease physical activity during pregnancy has been shown to be effective for improving patients' outcome and the prevention of unwanted occurrences such as prematurity (24). However, there is currently no evidence to support or refute its implementation for women who are exposed to lifting during pregnancy. Due to the aforementioned inconclusive nature and the methodological flaws in available studies, an RCT is needed to fill the gap.